Results of urogenital fistulas repair using caravan approach in Côte d’Ivoire (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To report the experience of surgical caravans for urogenital fistulas care.Methods: It was a retrospective study covering the period from January 1st 2014 to December 31st 2014 and which took place on 7 sites of fistula care. The epidemiological, anatomic, clinical, therapeutic and evolutionary aspects were studied. Recruitment was made by radio announcements and word of mouth approaches. Treatment was free of charge for patients.Results: During 14 caravans 346 patients were operated. Their mean age was 33.11 years (12 - 70 years). Most of these patients were without remunerative activities (80%) and without education (63.3%). They had been living with fistula for 6.08 years on average (0 to 42). Obstetrical etiology was predominant (87.9%), the otherswere iatrogenic and traumatic. According to the Kees Waaldijk classification, fistulas were distributed as follows: type I (67.4%), type II Aa (12.7%), type II Ab (8.4%) and type III (11.5%). The most common surgical approach was the transvaginal route (82.1%). The vesicovaginal splitting with separated suture of the bladder and the vagina was the basic technique (94.7%). The therapeutic results were judged after a follow-up of 1 month and 3 months. Lost to follow-up within that period was 23% i.e. 80 patients in month one and 70% (245 patients) at month three. The success rates evaluated in patients reviewed at month one and at  month  3 were respectively 70% and 64%.Conclusions: Caravan approach to recruit patients with fistula was feasible using local advertisements mans. Patients have been living with fistula for long time. Follow-up was difficult at Month 3.